Si-Miao-Yong-An Decoction Protects Against Cardiac Hypertrophy and Dysfunction by Inhibiting Platelet Aggregation and Activation - Su, Congping; Wang, Qing; Zhang, Huimin; Jiao, Wenchao; Luo, Hui; Li, Lin; Chen, Xiangyang; Liu, Bin; Yu, Xue; Li, Sen; Wang, Wei; Guo, Shuzhen (Frontiers in Pharmacology, 2019)
Objective: The aim of this study was to determine whether Si-Miao-Yong-An decoction (SMYAD) could ameliorate pressure overload-induced heart hypertrophy and its mechanisms. Methods: C57BL/6 mice were subjected to either sham or transverse aortic constriction (TAC) surgery to induce heart hypertrophy. SMYAD (14.85 g/kg/day, ig) or captopril (16.5 mg/kg/day, ig) was administered to the mice for 4 weeks. Cardiac function was evaluated based on echocardiography. Heart hypertrophy was detected using hematoxylin and eosin or wheat germ agglutinin staining. Protein expression of CD41, CD61, and P-selectin were measured with Western blot and immunohistochemistry. The expression levels of atrial natriuretic peptide, brain natriuretic peptide, β-myosin heavy chain, β-thromboglobulin, and von Willebrand factor were evaluated by quantitative polymerase chain reaction. Results: Four weeks after TAC, mice developed exaggerated cardiac hypertrophy and demonstrated a strong decrease in left ventricular ejection fraction compared with sham (29.9 ± 9.3% versus 66.0 ± 9.9%; P < 0.001). Conversely, SMYAD improved cardiac dysfunction with preserved left ventricular ejection fraction (66.5 ± 17.2%; P < 0.001). Shortening fraction was increased by SMYAD, while the left ventricular internal diameter and left ventricular volume were decreased in SMYAD group. SMYAD treatment significantly attenuated cardiac hypertrophy as reflected by the inhibition of atrial natriuretic peptide, brain natriuretic peptide, β-myosin heavy chain mRNA expression, and by the decreasing of cardiac myocyte cross-sectional area. Furthermore, Western blot and immunohistochemistry indicated that the protein expression of platelet aggregation markers (CD41 and CD61) and platelet activation marker (P-selectin) were significantly higher in model mice compared with control. These pathological alterations in TAC-induced mice were significantly ameliorated or blocked by SMYAD administration. Conclusions: Our results suggested that SMYAD exerted its effect by inhibiting platelet aggregation and activation as revealed by CD41/CD61/P-selectin downregulation. Inhibition the activation of the platelets might contribute to the therapeutic effect of SMYAD in failing heart.